2021
DOI: 10.3389/fphys.2021.717571
|View full text |Cite
|
Sign up to set email alerts
|

The Abscopal Effects of Cranial Irradiation Induce Testicular Damage in Mice

Abstract: To investigate whether the abscopal effects of cranial irradiation (C-irradiation) cause testicular damage in mice, male C57BL/6 mice (9weeks of age) were randomly divided into a sham irradiation group, a shielded group and a C-irradiation group and administered sham/shielded irradiation or C-irradiation at a dose rate of 2.33Gy/min (5Gy/d for 4 d consecutively). All mice were sacrificed at 4weeks after C-irradiation. We calculated the testis index, observed testicular histology by haematoxylin-eosin (HE) stai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Inconsistent timing of damage of the testis with this study, it is considered that the time of ionizing radiation-induced abscopal effects on testis damage is inconsistent due to the different thoracic irradiation area and irradiation dose fraction mode. In a previous study, fractionated X-ray cranial irradiation (5 Gy × 4) in mice was found to damage the structure and function of the testis, ultimately reducing sperm quality in mice at 4 W (Guo et al, 2021). This is consistent with our results, suggesting that the testis is the abscopal target of thoracic ionizing radiation.…”
Section: Discussionsupporting
confidence: 92%
“…Inconsistent timing of damage of the testis with this study, it is considered that the time of ionizing radiation-induced abscopal effects on testis damage is inconsistent due to the different thoracic irradiation area and irradiation dose fraction mode. In a previous study, fractionated X-ray cranial irradiation (5 Gy × 4) in mice was found to damage the structure and function of the testis, ultimately reducing sperm quality in mice at 4 W (Guo et al, 2021). This is consistent with our results, suggesting that the testis is the abscopal target of thoracic ionizing radiation.…”
Section: Discussionsupporting
confidence: 92%
“…The protocols of cranial irradiation and rTMS intervention have previously been reported [ 16 ]. Briefly, the mice were kept in a fixator to remain stable and conscious, and received cranial X-ray irradiation 5 Gy/d for consecutively 4 d at a dose rate of 2.33 Gy/min.…”
Section: Methodsmentioning
confidence: 99%